Strength of syllabic influences on articulation in Mandarin Chinese and French: Insights from a motor control approach. (November 2015) - Ma, Liang; Perrier, Pascal; Dang, Jianwu
Abstract: This paper investigates how strong the influences of syllables are on the organization of speech movements in Mandarin Chinese and French. More specifically, we evaluate the strength of these influences by measuring the extent of anticipatory coarticulation in V1 CV2 sequences, within and across the boundaries of the CV2 syllable. In line with motor control studies that have investigated serial-order motor tasks such as speech production, we consider that the extent of anticipatory motor planning reveals information about the units of planning, their boundaries and their strengths. For V1 /t/V2 and V1 /k/V2 sequences, where V1 and V2 are either /i/, /a/ or /u/, we used an electromagnetic magnetometer to record articulatory data from three native speakers of Mandarin Chinese and three native speakers of French. We labeled key articulatory configurations for V1, C and V2 based on general articulatory criteria. Our two major findings are: (1) Within CV2 boundaries, coarticulation is strong for both groups of speakers; in French, the coarticulation patterns can be fully explained by anticipatory behavior, while in Mandarin Chinese other strategies might also be involved. (2) Across CV2 boundaries, anticipatory coarticulation is observed in numerous cases in French, while no significant anticipation can be noted in Mandarin Chinese. We conclude that these measures provide evidence for the hypothesis that the strength of the syllable as a unit of speech planning is more important in Mandarin Chinese than in French. Finally, we propose potential explanations for these differences. Highlights: Coarticulation in Mandarin Chinese is highly constrained by syllable boundaries. Anticipatory coarticulation in French goes across syllable boundaries. Coarticulation is influenced by the status of the syllable in the language.